2007
DOI: 10.1002/cne.21457
|View full text |Cite
|
Sign up to set email alerts
|

The excitatory thalamo‐“cortical” projection within the song control system of zebra finches is formed by calbindin‐expressing neurons

Abstract: The learning and production of vocalizations in songbirds are controlled by a system of interconnected brain nuclei organized into a direct vocal motor pathway and an anterior forebrain (pallium-basal ganglia-thalamo-pallial) loop. Here we show that the thalamo-pallial ("thalamo-cortical") projection (from the medial part of the dorsolateral thalamic nucleus to the lateral magnocellular nucleus of the anterior nidopallium--DLM to LMAN) within the anterior forebrain loop is composed of cells positive for the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 92 publications
(150 reference statements)
0
15
0
Order By: Relevance
“…The border between CORE and SHELL regions of LMAN can be distinguished based on the density of magnocellular somata (Figure f), and the outer borders of SHELL can be distinguished from surrounding regions based on the intensity of neuropil staining. Some brains were stained immunohistochemically for calbindin, which specifically labels thalamic axons projecting to LMAN (Figure d, lower panel) (Achiro & Bottjer, ; Pinaud et al, ). Calbindin expression defined the outer borders of LMAN‐SHELL precisely, and revealed that even small injections into dNCL SHELL produced retrograde label within regions immediately surrounding SHELL ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The border between CORE and SHELL regions of LMAN can be distinguished based on the density of magnocellular somata (Figure f), and the outer borders of SHELL can be distinguished from surrounding regions based on the intensity of neuropil staining. Some brains were stained immunohistochemically for calbindin, which specifically labels thalamic axons projecting to LMAN (Figure d, lower panel) (Achiro & Bottjer, ; Pinaud et al, ). Calbindin expression defined the outer borders of LMAN‐SHELL precisely, and revealed that even small injections into dNCL SHELL produced retrograde label within regions immediately surrounding SHELL ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…In seven brains, the alternate series was stained for calbindin using established immuno‐histochemical procedures. Calbindin expression specifically labels thalamic axons terminating in LMAN (Achiro & Bottjer, ; Pinaud, Saldanha, Wynne, Lovell, & Mello, ) and delineates the borders of LMAN‐SHELL precisely (Figure d, lower panel). Briefly, birds were perfused with 4% paraformaldehyde (PFA) containing 0.4% glutaraldehyde, and brains were post‐fixed in 4% PFA for 30–50 hr before being immersed in 30% sucrose.…”
Section: Methodsmentioning
confidence: 99%
“…Johnson et al 1995 [43] and Bottjer et al [92] noted that DLM had a dorsolateral part that projects to LMAN, and a ventromedial part that projects to the nidopallium around LMAN. Based on calbindin expression and other evidence, Pinaud et al [93] proposed calling these areas the DLM core and shell, respectively, and argued that the surrounding area is really a larger DLM structure. We believe that all of these different designations (aDLM, DLM core, and dorsolateral DLM) refer to the same area that is connected to the song system, which we prefer to call aDLM, as an anterior specialized part of DLM.…”
Section: Discussionmentioning
confidence: 99%
“…Clones were originally obtained by screening a λgt10 cDNA library, through polymerase chain reaction (PCR) cloning or derived from the ESTIMA clone collection, which is publicly available at http://titan.biotec.uiuc.edu/cgi-bin/ESTWebsite/estima_start?seqSet=songbird (Mello et al. , 1992; Pinaud et al. , 2004, 2007; Replogle et al.…”
Section: Methodsmentioning
confidence: 99%